Coronary balloon angioplasty for elderly patients with severe angina. Issue 5 (November 1987) - Urban, P; Fox, K; Crean, P; Shapiro, L; Rickards, A
Abstract : From February 1983 to December 1986, 65 angioplasty procedures were attempted in 51 patients aged 65 or more. All had angina refractory to medical treatment and 89% of procedures were performed in patients in Canadian Cardiovascular Society angina class III or IV. Sixty eight per cent of patients had multivessel disease. Angioplasty was attempted on a single vessel in 52 instances (80%) and on multiple vessels in 13 (20%). The initial success rate was 75% for stenosis and 44% for occlusion. No attempt was made to treat all visible lesions in every case. At least one major complication occurred in 6.2% of the procedures: Q wave infarction in 4.6%, emergency surgery in 4.6%, and death in 4.6%. After a median follow up of four months (range 1-31) 37% of the patients in whom the procedure was initially successful were asymptomatic and 76% were improved by at least one Canadian Cardiovascular Society angina class. Angiographic restenosis occurred in 28% of treated lesions and 39% of patients had at least one recurrent stenosis. Among the patients with an initially successful procedure, 11% needed surgical revascularisation during the follow up period compared with 50% of those with a failed angioplasty. Balloon coronary angioplasty can be an effective form of treatment for the relief of severe angina in elderly patients.